ผลของการแทนที่ฟลาวร์ข้าวสาลีด้วยฟลาวร์พืชทนแล้งต่อพฤติกรรมการเกิดเพสต์ สมบัติของ ขนมปัง และการเปลี่ยนแปลงคุณภาพของขนมปังในระหว่างการเก็บรักษา - ธนจันทร์ มหาวนิช (มหาวิทยาลัยสยาม, 2022)
This study investigated pasting behavior of flour blends of wheat and drought-resistant crops (DRC), namely Job’s tears, millet, and chickpea, as well as to develop a bread product from such flour blends. Wheat flour was substituted with DRC flours at 3 different levels (10, 20 and 30% by weight). Regarding pasting behavior, DRC flour-substituting samples demonstrated reduced peak, trough, and breakdown viscosities as compared to the all-wheat control (p≤0.05). Adding Job’s tears or chickpea flour resulted in a decrease in pasting temperature as well as final and setback viscosities as compared to the control. Meanwhile, millet flour substitution did not affect such pasting properties. Upon substituting wheat flour in a bread recipe with DRC flour, the bread exhibited lower specific loaf volume than the control (p≤0.05). DRC flour substitution was shown to pose an effect on color of bread crust and crumb. Pertaining to textural properties, DRC flour addition caused an increase in hardness and chewiness of either freshly baked (Day 0) or stored bread samples. On the other hand, freshly baked DRC flour-containing breads exhibited lower springiness and cohesiveness than the control. However, upon storage, springiness and cohesiveness of the DRC flour-containing breads were similar to those of the control. Based on monitoring starch retrogradation, it was found that the breads with DRC flour had lower water-soluble starch content than the control for which the content became reducing with increasing substitution level.